2017
DOI: 10.1038/s41598-017-05241-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suspended sediments on the sponge holobiont with implications for dredging management

Abstract: Dredging can cause high suspended sediment concentrations (SSC) in the water column, posing a hazard to filter feeding organisms like sponges as sediment may clog their aquiferous systems and reduce feeding. In order to provide pressure−response values for sponges to SSC and tease apart the cause:effect pathways of dredging pressures, five heterotrophic and phototrophic species were experimentally exposed to a range of dredging-relevant SSC of up to 100 mg L−1, with light compensation across treatments to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…, Pineda et al. , b), there is still a major knowledge gap about how sponge‐associated macrofauna respond to these environmental pressures and how this impacts host health and fitness.…”
Section: How Might Other Changes On Reefs Directly or Indirectly Inflmentioning
confidence: 99%
“…, Pineda et al. , b), there is still a major knowledge gap about how sponge‐associated macrofauna respond to these environmental pressures and how this impacts host health and fitness.…”
Section: How Might Other Changes On Reefs Directly or Indirectly Inflmentioning
confidence: 99%
“…Sponge holobionts play a key role in marine ecosystems, contributing to reef formation, benthic-pelagic nutrient coupling, and biogeochemical cycling (30)(31)(32). Some of these sponge-microbe associations are highly stable under environmental stressors, including elevated temperature (33)(34)(35), eutrophication and sedimentation (36), and some symbionts are spongespecific, meaning they occur negligibly in the environment (37). Stable sponge-microbe associations were also found across large geographic distances (38).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental loss of symbionts in C. orientalis as a result of thermal stress has been observed before, and can cause longer-term energetic deprivation and mortality to the holobiont (Fang et al, 2013a(Fang et al, , 2014; Chapter 4 of the present thesis). Cnidaria that are symbiotic with Symbiodinium may compensate for the loss of phototrophic capacity by increasing their heterotrophic potential (Grottoli et al, 2006;Dove et al, 2013), but the presence of such plasticity in photosymbiotic sponges is debatable and could not be confirmed here (Fang et al, 2014(Fang et al, , 2017(Fang et al, , 2018Pineda et al, 2017b; Chapter 4 of the present thesis). In our experiment, heterotrophic uptake of carbon was generally higher by day than by night regardless of the treatment, which is in accordance with higher pumping rates of C. orientalis by day .…”
Section: Photosynthesis and Bioerosion Ratesmentioning
confidence: 86%
“…A handful of studies have shown that bioeroding sponges that host Symbiodinium erode faster when exposed to sunlight (Rosell and Uriz, 1992;Hill, 1996;Schönberg, 2006) and that decreases in light availability affect the holobiont negatively (Pineda et al, , 2017a(Pineda et al, , 2017b, but the mechanism behind such observations remains elusive. In such bioeroding sponges, one may ponder on the intriguing possibility that photosynthetic products may stimulate bioerosion.…”
Section: Photosymbiotic Bioeroding Spongesmentioning
confidence: 99%
See 1 more Smart Citation